GELIAT PENGEMBANGAN PROGRAM KEPENDUDUKAN DAN KELUARGA BERENCANA DI KECAMATAN RUPAT UTARA - Nur Laila Meilani; Ali Yusri; Hesti Asriwandari (Halu Oleo University, 2022)
This study discusses the population problem with the parameters of birth rate, death rate and population movement (migration). This research was conducted in North Rupat District. The purpose of this study is to describe the population profile in the North Rupat sub-district by describing through fertility, mortality and migration data and to analyze the Family Planning Program which also targets the Akit Tribe Indigenous Community in North Rupat District. This study uses a qualitative approach at the level of data collection and analysis. Data were collected through in-depth interviews, surveys, and observations in Titiakar Village, Ayu Forest, and Tanjung Medang. The results of this study indicate that in the aspect of implementing the Family Planning (KB) program, several challenges that need immediate intervention were identified, such as the limited choice of family planning methods, preferences about the gender of children based on mythology, motivation for family planning and local leadership factors. Several practical/policy implications are presented in this study.